Comet assay application for determining genotoxicity of veterinary vaccines preparations - Dybkova, S.M.; Roman'ko, M.E.; Gruzina, T.G.; Rieznichenko, L.S.; Ulberg, Z.R.; Ushkalov, V.O.; Golovko, A.M. (Вiopolymers and Cell, 2010)
Aim. To study a possibility of usage of the alkaline gel electrophoresis method (Comet assay) for determination of genotoxic properties of veterinary vaccines preparations. Methods. The alkaline gel electrophoresis of isolated eukaryotic cells has been used with further visualization of the samples by fluorescent microscopy. Results. Veterinary vaccines testing by the Comet assay method under alkaline conditions revealed that the samples No.1 and No 12 from twelve investigated vaccine preparations had genotoxic influence on eukaryotic cells of CHO-K1 and Vero test cultures, No. 12 sample being genotoxic only at metabolic activation. Conclusions. The method of alkaline gel electrophoresis of single cells (Comet assay) is suitable for determination of veterinary vaccines genotoxic influence on the test eukaryotic cells CHO-K1. The method proposed in this paper is express, inexpensive and predictive. The accompli-hed experimental work allows us to recommend this method for characterization of biosafety of veterinary vaccines preparations. Мета. Вивчити можливість застосування методу лужного гель-електрофорезу (методу ДНК-комет) для визначення генотоксичних властивостей ветеринарних вакцин. Методи. Використано метод лужного гель-електрофорезу ізольованих еукаріотних клітин з наступною візуалізацією досліджуваних препаратів за допомогою флуоресцентної мікроскопії. Результати. Тестуванням ветеринарних вакцин методом ДНК-комет за лужних умов виявлено, що двом зразкам вакцин із 12 досліджених (№ 1 та № 12) притаманна генотоксична дія стосовно тестових еукаріотних клітин культур СНО-К1 і Vero. При цьому зразок № 12 демонструє генотоксичні властивості лише за умови його тестування в системі метаболічної активації. Висновки. Метод лужного гель-електрофорезу ізольованих клітин (ДНК-комет) є придатним для визначення генотоксичного впливу ветеринарних вакцин на тестові еукаріотні клітини СНО-К1. Перевагами пропонованого методу є його експресність, низька вартість проведення досліджень і висока прогностичність отриманих результатів. Виконаний комплекс експериментальних робіт дозволяє рекомендувати зазначений метод для характеристики біобезпеки препаратів ветеринарних вакцин. Цель. Изучить возможность использования метода щелочного гель-электрофореза (метода ДНК-комет) для определения генотоксических свойств ветеринарных вакцин. Методы. Использован метод щелочного гель-электрофореза изолированных эукариотных клеток с последующей визуализацией исследуемых препаратов с помощью флуоресцентной микроскопии. Результаты. Тестированием ветеринарных вакцин методом ДНК-комет в щелочных условиях выявлено, что препараты вакцин № 1 и № 12 из 12 исследованных обладают генотоксическим действием на тестовые эукариотные клетки культур СНО-К1 и Vero, причем препарат № 12 демонстрирует генотоксические свойства только при тестировании в системе метаболической активации. Выводы. Метод щелочного гель-электрофореза изолированных эукариотных клеток (ДНК-комет) пригоден для определения генотоксического влияния ветеринарных вакцин на тестовые эукариотные клетки СНО-К1. Преимуществами предлагаемого метода является его экспрессность, низкая стоимость выполнения исследований и высокая прогностичность полученных результатов. Выполненный комплекс экспериментальных работ позволяет рекомендовать этот метод для характеристики биобезопасности препаратов ветеринарних вакцин.